Five ways to get a grip on teaching advocacy in medical education: The health humanities as a novel approach - Dhara, Arundhati; Fraser, Sarah (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2024)
The advocate role is recognized as an intrinsic medical competency. Despite recent attention to pedagogical approaches, it is a role that remains poorly understood and difficult to teach. At the same time there is a growing body of evidence showing the necessity of incorporating humanities-based education into medical curricula. Here, we present five ways to use the humanities as a tool for teaching the advocate role including: decentre the physician as expert, develop engaged providers, engage learners in curricular decisions, value the humanities (and show it), and keep it practical.